2021
DOI: 10.1016/j.ejca.2021.04.026
|View full text |Cite
|
Sign up to set email alerts
|

European trends in breast cancer mortality, 1980–2017 and predictions to 2025

Abstract: Background: Breast cancer mortality in European women has been falling for three decades. We analysed trends in mortality from breast cancer in Europe over the period 1980 e2017 and predicted number of deaths and rates to 2025. Methods: We extracted death certification data for breast cancer in women for 35 European countries, between 1980 and 2017, from the World Health Organisation database. We computed the age-standardised (world standard population) mortality rates per 100,000 person-years, by country and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 32 publications
1
42
0
2
Order By: Relevance
“…However, Wojtyla et al did not analyze trends in BC mortality by 5-year age groups. 34 According to Carioli et al, reduction in overall BC mortality was the smallest within the European Union; similarly, in a study by Malvezzi, OC mortality in 2002–2012 showed a small reduction. 35 , 36 In the first decade of the 21st century, a reversal in the CUC mortality trend, from declining or stable to significantly increasing or an acceleration of an increasing trend, was found in all women age ≥50 years.…”
Section: Discussionmentioning
confidence: 92%
“…However, Wojtyla et al did not analyze trends in BC mortality by 5-year age groups. 34 According to Carioli et al, reduction in overall BC mortality was the smallest within the European Union; similarly, in a study by Malvezzi, OC mortality in 2002–2012 showed a small reduction. 35 , 36 In the first decade of the 21st century, a reversal in the CUC mortality trend, from declining or stable to significantly increasing or an acceleration of an increasing trend, was found in all women age ≥50 years.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, Baeyens-Fernández et al, found a five-year survival rate in Granada (Spain) of 83.7% in a cohort of women with a BC diagnosed in 2010-2012 (n = 8.502) [22]. Nevertheless, the overall survival rate after BC was lower than Northern European countries, the USA or Australia [23,24], probably due to a socioeconomic gap in favor of these countries, which conditions more innovative treatment options, better established screening programs and more advanced diagnoses [25]. The lower survival rate in Spain is important to understand our findings related to the lower survival of Spanish women with BC and T2DM [17], which is the age group with higher mortality rates after BC, according to our results, their survival rate may have been overestimated.…”
Section: Discussionmentioning
confidence: 99%
“…All these factors should be considered during the implementation of subsequent national preventive programs, especially for women with reduced values of assets. Financial support for these women is essential, especially in current times, when increasing mortality and morbidity of breast cancer in Poland is observed [ 30 ].…”
Section: Discussionmentioning
confidence: 99%